2011
DOI: 10.1111/j.1469-0691.2010.03312.x
|View full text |Cite
|
Sign up to set email alerts
|

Whole body [18F]fluorodeoxyglucose positron emission tomography imaging for the diagnosis of pacemaker or implantable cardioverter defibrillator infection: a preliminary prospective study

Abstract: We studied the potential use of [(18) F]fluorodeoxyglucose ((18) F-FDG) whole body positron emission tomography (PET)-computed tomography for the diagnosis of device infection and extension of infection. Twenty-one patients with suspected device infection were prospectively included and compared with 14 controls free of infection. (18) F-FDG uptake on the box and on the leads was visually and quantitatively interpreted (using the maximal standard uptake value). The final diagnosis was obtained either from bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(97 citation statements)
references
References 13 publications
4
82
0
4
Order By: Relevance
“…For leads, sensitivity and specificity are lower, and diagnosis is based upon visualization of mild focal uptake along the leads. Interpretation of negative cases should be cautious, particularly if patients have received prolonged antibiotherapy (Bensimhon et al, 2010).…”
Section: Positive Emission Tomography (Pet)mentioning
confidence: 99%
“…For leads, sensitivity and specificity are lower, and diagnosis is based upon visualization of mild focal uptake along the leads. Interpretation of negative cases should be cautious, particularly if patients have received prolonged antibiotherapy (Bensimhon et al, 2010).…”
Section: Positive Emission Tomography (Pet)mentioning
confidence: 99%
“…15,18,22,[26][27][28][29][30][31] However, one caveat is that the majority of studies evaluating diagnostic accuracy in suspected CIED-GPI only include confirmed cases or those with medium-to-high pre-test probability. Paradoxically, patients at the opposite end of the spectrum (with a lower pre-test probability of infection at initial presentation) are generally considered to pose a greater diagnostic challenge and by comparison are relatively underrepresented in these studies; arguably, a novel non-invasive diagnostic tool would be most useful in this group of patients, and further studies assessing the performance of 18 F-FDG in this group are desirable.…”
Section: Historical Perspectivementioning
confidence: 99%
“…For improving the accuracy of the Duke criteria, other imaging modalities such as multidetector computed tomography (CT), 18 F-fluorodeoxyglucose (FDG) positron emission tomography (PET), and single-photon emission computed tomography (SPECT) have recently gained importance. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] With the use of retrospective ECG-gated acquisitions and intravenous contrast to enhance vascular structures, currentgeneration CT scanners provide enough spatial detail to visualize the valvular structures at several different phases of the cardiac cycle without motion artifact. The so-called cardiac CT angiography (CTA) is possibly superior to TEE for the evaluation of perivalvular complications such as abscesses and pseudoaneurysms or fistulae.…”
Section: Article See P 1113mentioning
confidence: 99%